PEMANFAATAN TEKNOLOGI TEPAT GUNA MESIN PENGIRIS TEMPE UNTUK MENINGKATKAN PRODUKTIFITAS UMKM KERIPIK TEMPE DI DESA SILIRAGUNG KECAMATAN SILIRAGUNG - Trianasari Ely; Pamuji Ridlo Dian; Prayogo Sandy Galang; Rahayu Sri Ninik (ROTOR, 2017)
Tempe is a favorite food of Indonesian society either from the bottom to the upper class of society. In addition to the cheap price, protein and other nutrients in tempe can meet some of the daily nutritional needs of Indonesian society. As soybean, tempe can also be processed into several foods that are tasty, nutritious and have high economic value. One of processed products using tempe as raw material is tempe chips. Given the increasing prices of basic needs that exist today, many people do small and medium enterprises to meet the basic needs. One of them is by doing tempe chips business. Nowadays, a lot of small business community found selling tempe chips, one of which is in the Siliragung, Banyuwangi. Because the taste is tasty and crunchy, tempe chips are much preferred. In designing the machine, partners and students of Mechanical Engineering Program are involved. The initial phase of this devotional activity is to conduct a survey in order to identify problems faced by partners and conduct a literature study to find solutions to partner problems. After the solution of partner problems obtained, the next step is to design the required machine that is tempe slicing machine. The machine to be made is expected to help the community in increasing the productivity / production capacity of tempe chips compared with manual or traditional process so that the production time can be shortened and the income of the society increases. Keywords: tempe slicing machine, tempe, productivity.